Comparação dos genótipos e frequencia dos alelos de ACTN3 de jogadores de futebol de diferentes categorias - Barbosa Coelho, D.; Mendonça Pimenta, E.; Cruz Rosse, I.; Santos Carvalho, M. R.; Gonçalves Costa, G.; Silami-Garcia, E. (Revista Brasileira de Ciência e Movimento, 2014)
The purpose of this study is to identify the genotypes and allele frequency of the ACTN3 polymorphism in Brazilian football players at different competitive levels. The ACTN3 gene encodes ?-actinin-3. A polymorphism in this gene (ACTN3 R577X) alters the expression of ?-actinin-3 and is associated with performance of strength and speed as the predominant activities. The study included 140 male players in professional (PRO) (N: 83, 23.3 ± 4.5 years), Under-14 (U-14) (N: 43, 14.5 ± 0.4 years) and amateur (AMA) categories (N: 14, 22.2 ± 3.43 years). The ACTN3 gene was genotyped by PCR-RFLP using the restriction enzyme DdeI. The frequencies of the ACTN3 variants, RR, RX and XX, were compared among the study groups. No significant difference was found between allele frequencies (p = 0.77). Decreased frequency of the XX variant and increased frequency of the RX variant were observed in the U-14 and PRO categories when compared to AMA (p = 0.03). This finding suggests the existence of artificial selection of football players with mixed characteristics (strength and resistance). Weaker individuals would tend to be excluded as the demand during training and competition increases.